Effects of Using the ISO 9001: 2015 Quality Management System on Customer Satisfaction with Quality Mediation Services at Sharia Bank - Hayati, Suci (International Journal of Psychosocial Rehabilitation, 2020)
The use of ISO 9001 as a quality management system standard has been widely used in companies, including in the sharia bank sector. This research was conducted to analyze the effect of implementing a Quality Management System (QMS) using ISO 9001: 2015 on customer satisfaction in service at the sharia bank. Data obtained from filling out the questionnaire by a customer at a Sharia Bank in the city of Bandar Lampung. The data obtained were processed by regression analysis using the SPSS program. The results showed that the implementation of the Quality Management System based on ISO 9001: 2015 in the bank had insignificant influence or in other words weak effect. However, this research also shows that the Quality Management System based on ISO 9001: 2015 significantly influences the quality of service at the bank.